Subcutaneous Phaeohyphomycosis Due to Pyrenochaeta romeroi Mimicking a Synovial Cyst - Dinh, Aurélien; Levy, Bruno; Bouchand, Frédérique; Davido, Benjamin; Duran, Clara; Cristi, Marin; Felter, Adrien; Salomon, Jérôme; Ait Ammar, Nawel (Frontiers in Microbiology, 2016)
Opportunistic subcutaneous fungal infections are increasing nowadays due to the growing number of medical conditions causing immunosuppression, especially organ transplant. The incidence rate of subcutaneous phaeohyphomycosis is very low. Most studies found are case reports. They showed a wide variation of clinical presentations. Pyrenochaeta romeroi, a fungus from the Dematiaceae group is a saprophyte found in soil and plants and a possible causative agent of phaeohyphomycosis. We present a rare case of subcutaneous phaeohyphomycosis caused by P. romeroi mimicking a synovial cyst in a diabetic patient.